2016
DOI: 10.1371/journal.pone.0152080
|View full text |Cite
|
Sign up to set email alerts
|

Social Learning in Vespula Germanica Wasps: Do They Use Collective Foraging Strategies?

Abstract: Vespula germanica is a social wasp that has become established outside its native range in many regions of the world, becoming a major pest in the invaded areas. In the present work we analyze social communication processes used by V. germanica when exploiting un-depleted food sources. For this purpose, we investigated the arrival pattern of wasps at a protein bait and evaluated whether a forager recruited conspecifics in three different situations: foragers were able to return to the nest (full communication)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
(51 reference statements)
5
12
0
Order By: Relevance
“…The curves of arrivals to multifida essential oil: ρ = −0.28, p = 0.31; α-terpinene: ρ = −0.04; n = 25, p = 0.87). Spearman's rank correlation ρ, α = 0.05 the untreated bait describe a non-linear pattern, which indicates the existence of local enhancement and recruitment to the food source, in accordance with what was observed by Lozada et al (2016). Meanwhile, the arrival pattern was linear and the slope of the curve significantly lower in treated baits.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The curves of arrivals to multifida essential oil: ρ = −0.28, p = 0.31; α-terpinene: ρ = −0.04; n = 25, p = 0.87). Spearman's rank correlation ρ, α = 0.05 the untreated bait describe a non-linear pattern, which indicates the existence of local enhancement and recruitment to the food source, in accordance with what was observed by Lozada et al (2016). Meanwhile, the arrival pattern was linear and the slope of the curve significantly lower in treated baits.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, nest recruitment has also been demonstrated in this species (Lozada, D'Adamo, Buteler, & Kuperman, 2016;Overmyer & Jeanne, 1998;Santoro, Hartley, Suckling, & Lester, 2015;Schueller, Nordheim, Taylor, & Jeanne, 2010;Taylor, Schalk, & Jeannem, 2010).…”
mentioning
confidence: 75%
“…; Lozada et al . ), although it is not clear why could this be occurring in terms of cost–benefit trade‐offs. Several authors have assessed that maladaptive behaviour can be found in various species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The global success of this species is mainly determined by its food plasticity, which makes it easily adaptable to different environments [4,5,6]. In fact, the European wasp is an opportunist predator and a scavenger because its eclectic diet includes small prey, vertebrate and invertebrate carrions, food and garbage from humans, and also carbohydrates from nectar, fruits and honeydew [7,8,9,10]. Coelho and Hoagland [11] reported that in the late summer and early autumn, German yellowjackets feed on dead honey-bees found at the ground level near hives.…”
Section: Introductionmentioning
confidence: 99%
“…germanica foragers are attracted by the presence of conspecifics at food sources by local enhancement processes [25,26] and they can influence other naive foragers to search for an odor sampled inside the nest [27]. Lozada et al [10] show that there is evidence of social communication for forager recruitment even at a distance from the resource: when foragers return to the nest after the foraging trip, the subsequent number of wasp foragers was approximately four times higher compared to when communication with the nest was not possible.…”
Section: Introductionmentioning
confidence: 99%